TONE MAPPING FOR IMAGE PROCESSING UNDER BRIGHT AMBIENT LIGHT ILLUMINATION - A. V. Sycev; A. A. Stepanov; A. G. Smirnov; K. .. Blankenbach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The measurement results of the brightness and color coordinates after the image transformation by using of tone mapping and color management, used in image processing under the influence of ambient light, in order to improve the reliability of reading information from the LCD are presented.